THE ANALYSIS OF THE REGIONAL INNOVATION SYSTEMS - CZECH CASE - Jan Stejskal; Katerina Matatkova (European Regional Science Association (ERSA), 2011)
Czech Republic does not belong among the leaders, whose economies are characterized by strong focus on innovation, science and research. To make the situation gradually improved, there the strategic documents and concepts must exist and also very specific tools to influence the formulation of the field at certain levels of state. Czech Republic still 10 years create, update and proceed accordingly according to these documents. But more pronounced shift to focus on innovation and their impact on competitiveness is not clear. The paper focuses on the analysis of the strategic framework for supporting regional innovation systems, their components and support for regional actors who are capable of producing innovation and commerce them. Contribution will be based on the current situation in the Czech Republic.
Keywords: 330